Rheumatoid arthritis: Pathogenic mechanisms and therapeutic targets - Taylor, P; Feldmann, M (2004)
Numerous novel therapies are in development for rheumatoid arthritis as a consequence of tremendous progress in understanding pathogenic mechanisms and defining relevant disease cells and molecules. Anti-tumour necrosis factor alpha (TNFα) therapies have been particularly successful and set a new standard for symptom control and attenuation of structural damage to joints. Other potential therapeutic targets across a variety of disease pathways have yet to be fully validated. These include pro-inflammatory cytokines, inflammatory cells and accessory molecules. © 2004 Elsevier Ltd. All rights reserved.